Comparative Analysis of the Health Level of Indonesian Islamic Banks (A Case Study of the Period Before and After the Merger) - Kunto Kiajar Giri; Widiyanti, Dwi Retno (Islamic Economics and finance in Focus, 2025)
This think about analyzes the contrasts in wellbeing levels of Bank Syariah Indonesia (BSI) sometime recently and after the merger of three state-owned Islamic banks utilizing the RGEC strategy (Chance Profile, Great Corporate Administration, Profit, and Capital). Information from quarterly money related reports from 2019–2023 were analyzed utilizing Matched Test t-test and Wilcoxon Signed-Rank Test on the proportions of NPF, PDN, ROA, and CAR. The comes about appear critical contrasts in all proportions, demonstrating that the merger had a genuine affect on BSI's execution and monetary steadiness. These discoveries fortify that mergers can improve the effectiveness and strength of Islamic banks, in spite of the fact that this ponder is still restricted to quantitative information and a moderately brief post-merger period.